Putting Your Heart to Sleep with Pentameters: A Prosodic, Lexical, and Syntactic Analysis of Fernando Pessoa’s Sonnet X - Portela, Manuel (2016)
This article analyses Fernando Pessoa’s Sonnet X (“As to a child, I talked my heart asleep”) as a modernist parody of the Shakespearean sonnet. The presence of that highly constrained form is clearly recognizable at the level of both versification and language. At the same time, a number of “marked and essential differences” indicate that this poem is not a mere stylistic or thematic imitation of its model. The text’s reflexive reference to the possibilities of splitting and binding sound to sense, on the one hand, and of splitting written self from writing self, on the other, highlight Pessoa’s awareness of a self who is constituted in and through language. Weaving word-as-sound and word-as-sense with self-as- grammatical person, the text becomes the material evidence for the self-inventing and self-deceiving nature of literary activity.